Aesthetic Effect of Autologous Fat Transplantation on Frontotemporal Depression Filling and Its Influence on SCL-90 and SES of Patients. (11th October 2022) - Yin, Dongjing; Shen, Guoliang
Abstract : Objectives . This study aimed to study the aesthetic effect of autologous fat transplantation in frontotemporal depression filling as well as the influence on the Symptom Checklist 90 (SCL-90) and the Rosenberg Self-Esteem Scale (SES) score of patients. Methods . A total of 100 patients with frontotemporal depression admitted to the outpatient department of burn and plastic surgery in our hospital were selected as the observation group, and all of them received autologous fat transplantation. The filling effect of patients in the observation group was discussed. Simultaneously, 50 volunteers were selected as the control group to compare the SCL-90 and SES scores of the observation group and the control group. Result . ① A total of 100 patients with frontotemporal depression were treated with autologous fat transplantation, and the secondary autologous fat transplantation rate was 10%; two cases of fat absorption occurred during the 12-month follow-up after surgery; on the 7 th day, 6 months, and 12 months after the operation, the satisfaction rate of the patients who visited the doctor was 96.00%, 97%, and 92.00%; the satisfaction rate of the plastic surgeon was 94.00%, 96%, and 90.00%; the satisfaction rate of the third party was 96.00%, 98%, and 92.00%. ② The preoperative scores of somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety, hostility, terror, paranoia, and psychotic factor scores in the observation group were higher than those in the control group (P < 0.05 ). The scores of somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety, hostility, terror, paranoia, and psychotic factor scores in the observation group at 6 months after the operation were lower than those before operation (P < 0.05 ). The preoperative SES score of the observation group (28.51 ± 9.81) was significantly lower than that of the control group (32.47 ± 5.39) (P < 0.05 ). The SES score (34.17 ± 9.81) in the observation group at 6 months after the operation was significantly higher than that before the operation (P < 0.05 ). Conclusion . The aesthetic effect of autologous fat transplantation in frontotemporal depression filling is good and safe. Simultaneously, it can improve the mental health and self-esteem of patients and has high clinical value.